Phage display selected magnetite interacting Adhirons for shape controlled nanoparticle synthesis1. Issue 10 (14th October 2015) - Rawlings, Andrea E.; Bramble, Jonathan P.; Tang, Anna A. S.; Somner, Lori A.; Monnington, Amy E.; Cooke, David J.; McPherson, Michael J.; Tomlinson, Darren C.; Staniland, Sarah S.
<x xml:space="preserve">Abstract</x> Biopanning was used to generate novel artificial binding proteins which are able to control the formation of synthetic cubic nanoparticles of magnetite.